Determining Effects of Superfine Sheep wool in INfantile Eczema (DESSINE): a randomized paediatric crossover study. (1st July 2017) - Su, J.C.; Dailey, R.; Zallmann, M.; Leins, E.; Taresch, L.; Donath, S.; Heah, S.S.; Lowe, A.J.
Summary: Background: Despite limited evidence, woollen clothing has traditionally been considered to be an irritant that should be avoided by individuals with atopic dermatitis (AD). Wool fibres come in a range of diameters, and have beneficial thermodynamic and moisture transport properties. Objectives: This study examines the effects of superfine merino wool on symptoms in participants with mild‐to‐moderate AD. Methods: The trial was a 12‐week, randomized, assessor‐blinded, crossover, prospective, cohort study of 39 patients with mild‐to‐moderate AD, aged between 4 weeks and 3 years, comparing superfine merino wool ensembles with standard cotton clothing chosen by parents. Participants were assigned to wool or cotton clothing and assessed every 3 weeks for 6 weeks, before crossing over to wear the other clothing material for a further 6‐week period, with similar 3‐weekly reviews. The primary end point was the SCORing Atopic Dermatitis (SCORAD) index after each 6‐week period, with Atopic Dermatitis Severity Index (ADSI), Infants' Dermatitis Quality Of Life Index (IDQOL) and topical steroid use as secondary end points to measure AD severity and quality of life. Results: Overall, compared with baseline, superfine wool ensembles were associated with a reduction in mean SCORAD of 2·5 [95% confidence interval (CI) −4·7 to −0·4] at 3 weeks and 7·6 (95% CI −10·4 to −4·8) at 6 weeks when compared with the cotton ensembles. A similar change was observed in ADSI and IDQOL scores for the same period. Body steroid use was also reduced. Conversely, changing ensembles from wool to cotton resulted in an increase in scores. Conclusions: Superfine merino wool may assist in the management of childhood AD.